Peningkatan Keterampilan Menulis dengan Menggunakan Layanan Informasi Berbasis Contextual Teaching and Learning (CTL) - Romi Fajar Tanjung (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2019)
Very important learning skills mastered to support the achievement of a learner, especially students who are already at a high level as well as the learning patterns demanded independence and maximum sincerity to be able to complete the study properly and on time. One of the skills learned are very important for a student namely writing skills. Student condition at the present time most have yet to master the technique of writing optimally, so that it could lead to underprivileged students write a scientific paper. This article is trying to improve student understanding of the writing skills by using a information service based Contextual Teaching and Learning (CTL). The sampling method using simple random sampling. The research sample is student counseling, amounting to 22 people. Analysis of the results using percentages and statistical tests using SPSS with the using Wilcoxon Signed Rank Test. The research found that the information services based Contextual Teaching and Learning (CTL) can significantly improve the writing skills of students with significant value of 0.005.